Effects of miR-204 on apoptosis and inflammatory response of Clostridium perfringens beta2 toxin induced IPEC-J2 cells via targeting BCL2L2. (July 2021) - Wang, Wei; Yang, Qiaoli; Huang, Xiaoyu; Luo, Ruirui; Xie, Kaihui; Gao, Xiaoli; Yan, Zunqiang; Wang, Pengfei; Zhang, Juanli; Yang, Jiaojiao; Zhang, Bo; Gun, Shuangbao
Abstract: Clostridium perfringens beta2 (CPB2) toxin can cause intestinal damage and inflammatory responses in a variety of animals, which seriously endanger the healthy development of animal husbandry. Increasing evidence has demonstrated that microRNAs (miRNAs) can play an important regulatory role in the process of pathogenic infection. In our previous study, we found that miR-204 was highly expressed in the ileum tissues of the susceptible group diarrhea piglets after infection with Clostridium perfringens ( C. perfringens ) type C. In this study, we found that miR-204 was also up-regulated in different time points after CPB2 toxin treatment. Overexpression of miR-204 promoted apoptosis and inflammatory response of intestinal porcine epithelial cells (IPEC-J2), whereas the opposite results were displayed after transfected with miR-204 inhibitor. Furthermore, the luciferase reporter assays confirmed that BCL2L2 was a direct target gene of miR-204. Interestingly, we found that overexpression BCL2L2 attenuated the apoptosis and inflammatory response of CPB2 toxin induced IPEC-J2 cells. In conclusion, these results find that miR-204 promotes the apoptosis and intensify inflammatory response of CPB2 toxin induced IPEC-J2 cells via targeting BCL2L2 . These data provide a valuable reference for the piglets resistance diarrhea at the molecular level. Graphical abstract: Image 1 Highlights: miR-204 is up-regulated during CPB2 toxin induced IPEC-J2 cells. miR-204 promotes IPEC-J2 cells apoptosis and inflammatory injury through directly targeting BCL2L2 . Overexpression BCL2L2 reversed the effects of miR-204 up-regulation on cell apoptosis and inflammatory response in CPB2 induced IPEC-J2 cells. These findings reveal a novel insights into the molecular mechanism in CPB2 toxin induced IPEC-J2 cells infection.